Implications of innovation policy instruments on the diffusion of biofuels for road transports - Gloria, Vanessa; Dyab, Linda (My University, 2017)
The transport sector accounts for a large share of released CO2 emissions to the atmosphere and employment of renewable alternatives are at this point highly demanded to combat climate change. One of the considered options to address the climate change issue is to use biofuels. However, transition towards sustainable transport using alternative technology such as biofuels might encounter multi-faceted challenges in the innovation and diffusion processes, which calls for implementation of innovation policy instruments. This thesis investigates the implications of innovation policy instruments on the diffusion of biofuels using cross-national comparative based case studies between Germany and Finland. Currently, Germany applies greenhouse gas (GHG) reduction quota as well as tax exemption and biofuels quota in the preceding years, while Finland implements biofuels obligation, taxation system and subsidy for new investments. Comparison between these different policy instruments may generate insights for mutual policy learning for other country, such as Sweden. Assessment of policy instruments in the case studies is based on the policy characteristics and their influences on the establishment of technological innovation functions/processes, which is reflected on the diffusion outcome in form of production and consumption levels of biofuels. The assessed characteristics comprise of stringency, flexibility, predictability, depth, differentiation, consistency, coherence, credibility and comprehensiveness; whereas the innovation processes consist of market formation, legitimation, resource mobilization, and reduced support for fossil fuels. Findings show that in Finland, production and consumption of biofuels have been growing progressively as a result of strong characteristics in the existing policy instrument mix that are able to settle the innovation functions/ processes impeccably. On the contrary, diffusion of biofuels in Germany is not optimized due to the weak policy instrument characteristics that all policy instruments have been having, and thus innovation functions/process have not been able to be established firmly. From the comparative analysis, several lessons can be taken for Sweden if it aims to diffuse biofuels, for example an instrument mix giving long term assurance for investments and good collaboration between actors like in Finland, as well as competition between biofuels suppliers and recurring legitimation issue in Germany that Sweden should avoid.
Keywords: Annan naturvetenskap; Other Natural Sciences